Use of Video Based Learning Media in Learning Fiqh: Meta-Analysis Study - Sihabudin Sihabudin; Almas Sharfina ‘Alaniah; Zakiyatul Nisa' (STAI Hubbulwathan Duri, 2023)
In fiqh learning, there are many complex laws, principles, and concepts where this requires encouragement that can improve students' way of thinking. The use of audio-visual learning media is one of the factors that can support this achievement. Video-based learning is a learning tool based on the use of video as a medium. This study aims to evaluate the effectiveness of the use of animated video instructional media in Islamic jurisprudence learning. Through the meta-analysis method, twenty national journal articles published between 2015-2023 that discussing the use of animated video-based instructional media in fiqh learning were analyzed. The results of the meta-analysis show that the use of animated video instructional media has a highly positive effect on fiqh learning at various levels of education, both elementary, junior high, and high school. Based on the topics of jurisprudence studied, the use of animated video learning media has a significant influence on the topic of procedures for ablution and pilgrimage. Meanwhile, a slightly lower influence occurred on the topic of procedures for prayer, fasting, and zakat. In addition, the use of animated video learning media also has a significant positive influence on learning aspects which include understanding concepts, learning motivation, critical thinking skills, and information retention. In terms of increasing understanding of fiqh concepts, the use of animated video learning media has a higher influence compared to other learning methods, such as power points, textbooks, and group discussions. This shows that animated video learning media is effective in helping students understand the concept of Islamic law better. The results of this study provide empirical evidence that supports the effectiveness of using animated video instructional media in Islamic jurisprudence learning.